(untitled) (Research, Society and Development, 2024)
Syphilis is a systemic infection caused by the bacterium Treponema pallidum and is one of the most prevalent STIs in Brazil. The aim of this study was to evaluate the sociodemographic profile of Gestational Syphilis (GS) and Congenital Syphilis (CS) cases in the municipality of Belém, state of Pará, Brazil, from 2018 to 2022. This is an original, descriptive and comparative study, carried out using secondary data from the Department of HIV/AIDS, Tuberculosis, Viral Hepatitis and Sexually Transmitted Infections (DVIAHV). The research was carried out in May 2023 and refers to notifications of confirmed cases of GS and CS. Sociodemographic variables were used: age group, schooling, race/color and treatment, and for CS: age group, schooling, race/color, treatment and prenatal care. The results of the five years studied showed a progressive increase in cases of GS, and a variable occurrence of CS, with a significant increase between 2018 and 2019, whose highest incidence rate was in women aged between 20 and 29, brown, with incomplete primary or secondary education. With regard to treatment, in SG a good number had it, and in SC there were more cases of non-adherence and inadequate treatment. With regard to prenatal care in CS, of the 612 women, 146 had not undergone it and 46 had done so incorrectly. Therefore, increasing measures for adherence, control and proper treatment guidance could generate favorable responses in the process of mitigating this problem.